Synthesis of P‐Stereogenic Tetraphosphacrowns. Issue 12 (15th October 2015) - Kato, Ryosuke; Morisaki, Yasuhiro; Chujo, Yoshiki
Abstract: Synthetic routes to enantiopure P‐stereogenic tetraphosphacrowns, containing four chiral phosphorus atoms, using a P‐stereogenic secondary bisphosphine are reported. 18‐Tetraphosphacrown‐6 and 24‐tetraphosphacrown‐8 derivatives were prepared by a single‐step and multistep method, respectively, and their characterizations are described in detail. Removal of boranes from the 24‐tetraphosphacrown‐8 derivative and subsequent complexation with platinum(II) are also described. Abstract : Chirali‐P : P‐Stereogenic tetraphosphacrowns containing four P‐stereogenic centers in the ring were synthesized by using a P‐stereogenic secondary bisphosphine as a key building block.